Tourism Gentrification in a Small Mediterranean Town: Impacts and Implications for Urban Climate Resilience - Kumer, Peter; Kralj, Erik; Meulenberg , Cécil (Journal for Geography, 2023)
This study explores the relationship between tourism gentrification and urban climate resilience in Piran. It focuses on socio-economic changes due to tourism and their implications for the town’s ability to respond to climate-related challenges. Using mixed methods, it evaluates the effects on architectural authenticity, public spaces, and community dynamics. The findings reveal conflicts between heritage preservation and tourism, highlighting integration challenges for newcomers in enhancing climate resilience. The paper advocates for strategies balancing sustainable tourism with cultural heritage preservation, offering solutions for similar towns in the Mediterranean.